Holistic Management: an approach to increase pasture sustainability and mitigate climate change effects - Catalán M.; Palomo G.; Moreno G. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Improving grazing management could increase soil carbon sequestration and other goods and services in grazing lands and contribute to increase pasture sustainability. The objectives of the study were to compare two grazing management techniques, one of them referring to holistic management. Nine plots, located in three farms in the Southwest of Iberian Peninsula under an Adaptive Multi-Paddock (AMP) grazing were compared with nine control plots of neighbouring farms with similar vegetation and soil and under a rotational stocking method. The analysed indicators were: Rangeland Health Index (RHI), plants richness and biodiversity, and soil quality like bulk density, total carbon and nitrogen, availability of phosphorous, calcium and potassium, microbial diversity and enzymatic activity. The results reveal better values of all indicators analysed in the AMP grazing plots in relation to control ones. Significant differences were found in percentage of ground cover, species richness, and availability of phosphorus and potassium (P<0,05). Although more studies are needed, these preliminary results show a trend to better health ecosystem and soil quality in the farms under AMP grazing. These findings highlight the importance of researching and implementing sustainable grazing managements to keep and restore grasslands thanks to ecosystem services generated by livestock, including carbon sequestration and climate regulation.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)